Two Years of SARS-CoV-2 Omicron Genomic Evolution in Brazil (2022–2024): Subvariant Tracking and Assessment of Regional Sequencing Efforts - Ueric José Borges de Souza; Fernando Rosado Spilki; Amilcar Tanuri; Paulo Michel Roehe; Fabrício Souza Campos (Viruses)
SARS-CoV-2, the virus responsible for COVID-19, has undergone significant genetic evolution since its emergence in 2019. This study examines the genomic diversity of SARS-CoV-2 in Brazil after the worst phase of the pandemic, the wider adoption of routine vaccination, and the abolishment of other non-pharmacological preventive measures from July 2022 to July 2024 using 55,951 sequences retrieved from the GISAID database. The analysis focuses on the correlation between confirmed COVID-19 cases, sequencing efforts across Brazilian states, and the distribution and evolution of viral lineages. Our findings reveal significant regional disparities in genomic surveillance, with São Paulo and Rio de Janeiro recovering the largest number of genomes, while Tocantins and Amazonas showed higher sequencing rates relative to their reported case numbers, indicating proactive surveillance efforts. We identified 626 distinct SARS-CoV-2 lineages circulating in Brazil, with dominant subvariants shifting over time from BA.5 in 2022 to XBB and JN.1 in 2023–2024. The emergence of new subvariants in this new epidemiological scenario underscores the importance of ongoing genomic surveillance to track viral evolution and inform public health strategies, providing valuable information to update vaccines and implement other measures, such as lockdowns, mask usage, social distancing, health education, and self-testing.